Lean tools and techniques: a comparison between Malaysian manufacturing and services organisations - Yahya, Mohd Shahir; Mohammad, Musli; Omar, Badrul; Ramly, Edly Ferdin (Science Publishing Corporation (SPC), 2018)
The purpose of this study is to compare lean tools and techniques in terms of the awareness, usage, effectiveness and potential future adoption between Malaysian manufacturing and services organisations in order to help Malaysian organisations to select, adopt and implement the right lean tools and techniques based their context. An online questionnaire survey of 114 respondents from 15 states in Malaysia was conducted. The quantitative data were gathered and analysed using the Statistical software. The findings of the survey indicated that there are no significance differences (p<0.05) between both manufacturing and services organisations for majority of lean tools and techniques. Nevertheless, Malaysian manufacturing organisations has indicated more prone to adopt some lean tools and techniques compared to services organisations.